OPTIMIZATION OF MACHINE PARTS DESIGN FOR EFFECTIVE ADDITIVE MANUFACTURING USING SOLIDWORKS SIMULATION - KUSHNIRCHUK, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Additive technologies have significantly improved the processes of creating complex-shaped structures with less weight and more efficient use of material. 3-D printing removes many restrictions on the shape of the product, which are present, for example, during the mechanical processing of parts on machine tools. The purpose of the work is to detail the features of using modern software tools, such as Solidworks Simulation, which will allow you to effectively integrate topology optimization into the 3D printing process, which helps to improve the quality of product design, its weight characteristics, reduce manufacturing time and production costs. Generative (toponymic) design methods can help for effective modeling of parts in CAD systems. Topological optimization and additive technologies allow you to obtain the final product without the need for additional processing. The article considers the use of topology research tools (Topology Optimization) to improve the 3D printing process of plastic products. Methods and approaches to creating optimal geometric configurations that ensure maximum product strength and efficiency are highlighted. The main aspects of the study include establishing initial conditions and constraints, determining the optimal topology to minimize weight or improve product functionality, and interpreting the results. Using modern software tools such as Solidworks Simulation, engineers can effectively integrate topology optimization into the 3D printing process, which helps improve quality and reduce production costs. The topology study improved product parameters and the 3D printing process for plastic products, namely, the weight of the product decreased by 50.7%, and the time to manufacture the part using FDM printing technology decreased by 53.7%.
Keywords: generative design method; optimization of part shape; mass minimization